The challenge of Genadendal - Du Preez, Hannetjie (IOS Press, 2009)
During our term in office as President of the Republic of South Africa, we decided to rename the presidential official residence in Cape Town from Westbrooke to Genadendal which means Valley of Grace. We also visited this historic little town on 10 October 1995. The renaming of the official residence was in honor of the oldest mission settlement in South Africa. Over the centuries it became a place associated with the coming together of people from different racial groups: in addition to being the first permanent Khoi settlement at the Cape, it was also a place of sanctuary for more than a tho.